Designers' guide to Eurocode basis of structural design : EN 1990 - Gulvanessian, H. (Designers' guides to the Eurocodes, 2012)
Eurocode 0, EN 1990: Basis of Structural Design is considered the primary document in the Eurocode suite which establishes for the structural Eurocodes the principles and requirements for safety and serviceability of structures. More importantly, EN 1990 must be applied whenever the Eurocodes 1 to 9 are used. This Designers' Guide was one of the first sources of detailed information on the use of EN 1990 and continues in this new edition to provide technical information on the background to the Eurocode and explains its relationship to the other Eurocodes. The background to the research-based principles and rules is discussed, emphasising the rules that differ from those in existing codes. Worked examples illustrate the use of new procedures.